ANALYSIS OF FACTORS AFFECTING HOTEL TAX REVENUE IN TASIKMALAYA CITY - Susilo, Haryono; Widyahayu, Widyahayu (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2022)
This study aims to prove the effect of Average Room Rate, Number of Tourists, and Constant Gross Regional Domestic Product (GRDP) on Hotel Tax Revenue in Tasikmalaya City. The data used in this study is data for 2018 2021 which aims to analyze Hotel Tax Revenues in Tasikmalaya City. By using secondary data sourced from the Regional Revenue Service of the City of Tasikmalaya and the Central Bureau of Statistics of the City of Tasikmalaya. Data analysis in this study used Multiple Linear Regression analysis using SPSS. The results of this study indicate that the average room rate has a positive and significant effect on Hotel Taxes, the number of tourists has a positive and significant effect on Hotel Taxes, and constant GRDP has a positive and insignificant effect on Hotel Taxes.